PERANCANGAN ARSITEKTUR INTERPRISE TERINTEGRASI MENGGUNNAKAN KERANGKA KERJA TOGAF ADM PADA SMP IBRAHIMY 3 SUKOREJO - Alfi Khairunnisa; Putri Anindya Damayanti; Akhlis Munazilin (Jurnal Riset Teknik Komputer, 2025)
The rapid development of information technology requires educational institutions to adopt structured and integrated information systems. SMP Ibrahimy 3 Sukorejo, a pesantren-based junior high school, still relies on many manual operational processes. This study aims to design an enterprise architecture using the TOGAF Architecture Development Method (ADM) to identify the school’s information system requirements. Data were collected through observation, interviews, and document analysis, and then analyzed according to the ADM phases. The results indicate the need for system integration in student admission, attendance, grade processing, and financial administration, supported by a centralized database and improved network infrastructure. The resulting enterprise architecture blueprint serves as a strategic reference for information system development and for enhancing the quality of educational services in pesantren-based schools.